Copper enhances genotoxic drug resistance via ATOX1 activated DNA damage repair. (28th June 2022) - Jin, Jing; Ma, Mingjun; Shi, Shaohui; Wang, Jiaru; Xiao, Pengyu; Yu, Hai-Fan; Zhang, Chao; Guo, Qiang; Yu, Ze; Lou, Zhenkun; Teng, Chun-Bo
Abstract: Copper is involved in various biochemical and physiological processes. The absorbed copper ions are transported to the intracellular destination via copper chaperones, such as ATOX1. Previous studies have demonstrated that neoplastic cells have a high demand for copper; however, its role in cancer cells has not been fully elucidated. Here, we reveal that the high level of copper contributes to drug resistance and repair of damaged DNA in cancer cells at least partially via ATOX1-induced expression of MDC1, a crucial protein involved in double-strand DNA damage repair. Specifically, ATOX1 enters into nuclear to target MDC1 promoter after treatments of various genotoxic agents, thus promoting the transcription of MDC1 in a copper-dependent manner. Therefore, knockout or blockage of ATOX1 conferred sensitivity to Gemcitabine in transplanted tumor mouse models. Together, our findings gain new insight into the role of copper in DNA damage repair and provide a novel strategy for clinical cancer therapy of drug-resistance cancers. Highlights: Copper ions benefits cancer cells on the resistance of genotoxic drugs and DNA damage. ATOX1 contributes to the Cu-dependent drug resistance via targeting MDC1 expression. ATOX1 inhibition together with GEM notably inhibit the growth of xenografted tumors.